1993
DOI: 10.1002/jsfa.2740610406
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive quality of the alkaloid‐poor Washington lupin (Lupinus polyphyllus lindl var SF/TA) as a potential protein crop

Abstract: An alkaloid-poor line of Washington lupin (Lupinus polyphyllus Lindl var SF/TA) was developed in an experiment started in 1982. The nutritive quality (alkaloid content, protein and amino acids, fat and fatty acids, macro-and micronutrients, fibre, sugars) yields, and seed quality of this line were studied. The results show that the total alkaloid content was low and varied in different seeds from 226 pg g-' to 366 pg g-' of dry matter. The main alkaloid was lupanine, but 16 other alkaloids (including sparteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…As a consequence, the alkaloid profile is more diverse in leaves than in seeds (Wink 1993) and L. campestris follows the same described pattern. Aniszewsky (1993) reported similar results for L. poZyphyZZus Lindl var SF/TA .…”
Section: M+= Molecular Ionsupporting
confidence: 63%
“…As a consequence, the alkaloid profile is more diverse in leaves than in seeds (Wink 1993) and L. campestris follows the same described pattern. Aniszewsky (1993) reported similar results for L. poZyphyZZus Lindl var SF/TA .…”
Section: M+= Molecular Ionsupporting
confidence: 63%
“…SF/TA that was obtained by crossing two genotypes found growing freely by the roadside in central Finland (Aniszewski, 1993a). The alkaloid-poor variety of Lupinus polyphyllus had multicoloured, grey, black and ®gured seeds (Aniszewski, 1993b). Previous studies have shown that it is possible to reduce the level of alkaloids in the Washington lupin by hybridization and to develop alkaloid-poor varieties which are potential crop species (Aniszewski, 1993a(Aniszewski, , b, 1994(Aniszewski, , 1995(Aniszewski, , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Because low‐alkaloid genotypes have for some time been developed through selection of either spontaneous or induced mutants for the main crop species L. angustifolius , L. luteus , L. albus , L. mutabilis , and some of the rough‐seeded lupine species (Gladstones, 1970; Clements et al, 2005), the trait can probably be developed in any lupine species for which it is considered viable. Low‐alkaloid genotypes of L. nootkatensis have been developed for use as green and processed fodder in Iceland (Plarre, 1991; Gudjónsson and Helgadóttir, 2000) and low‐alkaloid genotypes of L. polyphyllus have been bred (Aniszewski, 1993; Gudjónsson and Helgadóttir, 2000; Kurlovich, 2002). Breeding has continued in the development of permeable seed coats and reduced shattering for spring‐ and autumn‐sown L. polyphyllus for amelioration of eroded land and for grazing (Chekalin et al, 2001).…”
Section: Lupines As Modern Crop Plants: Challenges and Opportunitiesmentioning
confidence: 99%